Desenvolvimento profissional de professores do Instituto Federal da Bahia durante a pandemia de COVID-19 (2020-2021): um estudo no ensino médio integrado baseado na teoria fundamentada nos dados - Silva, Camila Lopes da (2022)
The present research aims to understand the teachers’ professional development process at the Federal Institute of Education, Science, and Technology of Bahia, who worked during the COVID-19 pandemic scenario in 2020 and 2021 years. In fact, a qualitative study was undertaken based on the Grounded Theory (GT), using the semistructured interview as a data collection instrument, in addition to the sociodemographic questionnaire to get to know the participants better. In total, 12 permanent teachers who worked in the integrated high school/secondary school at different IFBA campuses were interviewed. The results show that many teachers were not prepared for the transition between face-to-face teaching and remote teaching, and this adaptation generated numerous dilemmas and challenges in their professional development processes during this period. It was found that there is a demand for teacher education that meets the specificity of this teaching, for which the courses offered by the institution, in general, were not sufficient. Thus, the teachers needed to look for their own alternatives so that the main sources of their knowledge were self-education and their experience. The most mobilized didactic knowledge was the use of digital technology, evaluation and follow of learning processes and class time management. And the main lessons learned by teachers were linked to the use of technology in the educational context, the discovery of new methodological strategies for remote teaching, and the overcoming of limiting beliefs rooted in the thinking and doing of a teacher. Despite these advances, working conditions were marked by arrangement of domestic space and acquisition/use of equipment and furniture without adequate institutional support, increased working hours, and challenges related to mental health. The theoretical model built in this investigation allowed us to understand that, despite the difficulties of the pandemic, the teachers’ work in the remote teaching format contributed to they could advance in their professional development processes— considering that they needed to relearn how to teach in a new educational environment which is mediated by technology. Finally, the research also reveals the need to invest in teacher education and professional development policies, as well as in offering working conditions that contribute to teachers’ well-being and professional satisfaction.